Spinal cord stimulation for complex regional pain syndrome type 1 with dystonia: a case report and discussion of the literature - Voet, Caroline (F1000Research, 2014)
Background: Complex Regional Pain Syndrome type 1 (CRPS-1) is a debilitating chronic pain disorder, the physiopathology of which can lead to dystonia associated with changes in the autonomic, central and peripheral nervous system. An interdisciplinary approach (pharmacological, interventional and psychological therapies in conjunction with a rehabilitation pathway) is central to progress towards pain reduction and restoration of function. Aim: This case report aims to stimulate reflection and development of mechanism-based therapeutic strategies concerning CRPS associated with dystonia. Case description: A 31 year old female CRPS-1 patient presented with dystonia of the right foot following ligamentoplasty for chronic ankle instability. She did not have a satisfactory response to the usual therapies. Multiple anesthetic blocks (popliteal, epidural and intrathecal) were not associated with significant anesthesia and analgesia. Mobilization of the foot by a physiotherapist was not possible. A multidisciplinary approach with psychological support, physiotherapy and spinal cord stimulation (SCS) brought pain relief, rehabilitation and improvement in the quality of life. Conclusion: The present case report demonstrates the occurrence of multilevel (peripheral and central) pathological modifications in the nervous system of a CRPS-1 patient with dystonia. This conclusion is based on the patient’s pain being resistant to anesthetic blocks at different levels and the favourable, at least initially, response to SCS. The importance of the bio-psycho-social model is also suggested, permitting behavioural change.